2022
DOI: 10.1101/2022.01.01.474639
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

In vitro evaluation of therapeutic antibodies against a SARS-CoV-2 Omicron B.1.1.529 isolate

Abstract: The emergence and rapid spread of the Omicron variant of SARS-CoV-2, which has more than 30 substitutions in the spike glycoprotein, compromises the efficacy of currently available vaccines and therapeutic antibodies. Using a clinical strain of the Omicron variant, we analyzed the neutralizing power of eight currently used monoclonal antibodies compared to the ancestral B.1 BavPat1 D614G strain. We observed that six of these antibodies have lost their ability to neutralize the Omicron variant. Of the antibodie… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…Overall, our results indicate that AZD7442, when used as pre-exposure prophylaxis, has inhibitory activity in vivo against the Omicron BA.1 variant, although this activity is less than against a B.1 G614 virus. This is in line with previous results obtained in vitro [5][6][7][8][9][10] and a recent in vivo study in which a curative treatment with 5mg/kg of antibody cocktail, synthesized without any modification in their Fc region, efficiently inhibited the Omicron variant replication in lungs of hamsters 13 . The U.S. Food Drug Administration (FDA) has published pharmacokinetic data obtained after intramuscular administration of 300mg of AZD7442 14 , the dose used successfully in the PROVENT clinical trial (NCT04625725) 15 .…”
Section: Main Textsupporting
confidence: 92%
See 1 more Smart Citation
“…Overall, our results indicate that AZD7442, when used as pre-exposure prophylaxis, has inhibitory activity in vivo against the Omicron BA.1 variant, although this activity is less than against a B.1 G614 virus. This is in line with previous results obtained in vitro [5][6][7][8][9][10] and a recent in vivo study in which a curative treatment with 5mg/kg of antibody cocktail, synthesized without any modification in their Fc region, efficiently inhibited the Omicron variant replication in lungs of hamsters 13 . The U.S. Food Drug Administration (FDA) has published pharmacokinetic data obtained after intramuscular administration of 300mg of AZD7442 14 , the dose used successfully in the PROVENT clinical trial (NCT04625725) 15 .…”
Section: Main Textsupporting
confidence: 92%
“…Some of these mutations are associated with potential escape from humoral immunity and higher transmissibility 3,4 . Several in vitro studies have shown that monoclonal antibodies already used against SARS-COV-2 during the pandemic have reduced or no efficacy against the Omicron BA.1 variant [5][6][7][8][9][10] . In one of them, the activity of the combination of Cilgavimab/Tixagevimab (AZD7442) that targets the SARS-CoV-2 spike receptor binding domain (RBD) 11 and marketed by AstraZeneca as Evusheld, was reduced by a factor of ~40 5 .…”
Section: Main Textmentioning
confidence: 99%
“…Since therapeutics containing ACE2 run the risk of eliciting autoimmunity in humans, our use of ACE2 as the inhibitory component represents a proof-of-concept of the ReconnAb design. The ACE2 module could be replaced by other neutralizing components such as ACE2 domains with enhanced RBD-binding activity [72][73][74] , aptamers 75,76 , or RBD-directed mAbs [1][2][3][4][5][6][7][8][9]46,[56][57][58][59][60]77 . Future ReconnAb designs could also target the interaction with dipeptidyl peptidase 4 (DPP4), a receptor for other coronaviruses 78 , furthering their breadth.…”
Section: Discussionmentioning
confidence: 99%
“…The emergence of the Omicron variant has rendered six of the seven [1][2][3][4][5][6][7][8][9] clinically available monoclonal antibodies (mAbs) essentially ineffective against SARS-CoV-2 -only sotrovimab retains robust neutralizing activity against Omicron 10,11 . These clinical mAbs all target the receptor binding-domain (RBD) [1][2][3][4][5][6][7][8][9] of the spike protein and were selected for their neutralizing potency against Wuhan-Hu-1 SARS-CoV-2. The six mAbs besides sotrovimab target non-conserved (variable) regions of the RBD 4,[12][13][14][15][16][17][18] and prevent interaction with its receptor, human angiotensin converting enzyme 2 (ACE2) 16,[19][20][21] .…”
Section: Introductionmentioning
confidence: 99%
“…We used a standardised methodology for the evaluation of antiviral compounds based on the reduction of RNA yield 6 , which has been applied to SARS-CoV-2 3,7 . The assay was performed in VeroE6 TMPRSS2 cells and the amount of viral RNA in the supernatant medium was quanti ed by qRT-PCR 48h postinfection to determine the 50% effective concentration (EC 50 ).…”
Section: Mainmentioning
confidence: 99%